Diversity of earthworm species in Hoa Binh province - Le, Hoai Nam; Le, Xuan Son; Nguyen, Thi Trang; Nguyen, Hong Yen; Nguyen, Anh Duc; Tran, Thi Thanh Binh (Hue University Journal of Science: Natural Science, 2025)
This study presents research findings on earthworm diversity and distribution in Hoa Binh Province. These results were collected and evaluated based on previous research literature and specimens previously collected in the province. A total of 36 species belonging to 10 genera and six families were recorded in Hoa Binh Province. The family Megascolecidae accounted for 27 species in three genera, followed by Acanthodrilidae with four species in two genera. The family Ocnerodrilidae was recorded with two species in two genera, and one species each was recorded in the families Almidae, Moniligastridae, and Rhinodrilidae. Eight morphological species were identified at the generic level. The family Megascolecidae had seven morphological species, and the Moniligastridae family had one morphological species. The recorded earthworm species were mainly distributed at depths of 0–20 cm in timber and bamboo forest habitats. The number of recorded species is far from reflecting the true diversity of earthworms in Hoa Binh Province. Therefore, more intensive surveys are recommended to improve our knowledge of earthworm diversity in the province.